Reformation of Reproductive Health Using Havishyaanna in Rajaswalacharya - Sarika Trimbak Shinde (AYUSHDHARA, 2023)
It’s been years that women are suffering from general disturbances associated with menstruation like abdominal pain, psychological stress, disturbed bowel movements. PG inhibitors and antispasmodic drugs etc are the popular mode of medication used in regular gynaecological clinical practice. It can give relief to the patient but has limitations over preventing the recurrence, which is, tend to happen mainly in adolescent and middle aged women due to modern lifestyle. According to Ayurveda, menstruation is a physiological process and governed by the actions of the three balanced state Doshas exist in a proper and its inequality causes abnormal menstruation. There are amazing diets and lifestyle modification given in Ayurveda which are beneficial to restore menstrual health with different combinations given in the ancient texts. Amongst all given possible diets during menstruation, Havishyanna - special diet is the most feasible as patients can make it on its own, consume for first three days of menstrual cycle which requires very less timing and has simple procedure. Menstruating women can deal with symptomatic and psychological changes occur during the menstruation by practicing Rajaswala Paricharya. Addition to this Havishyanna helps to reform reproductive health, it maintains balance of Vata dosha during menstruation, proper Rajavahan and Rajasrav, proper Rutukal nirmiti which helps to form high quality of oocyte, maintain healthy uterine environment, all these able to carry healthy pregnancy, in turn healthy Progeny.